The Effect of Portfolio-based Assessment and Language Processing on Acquiring Second Language - Slamet Setiawan; Imroatul Karimah; Ahmad Munir (Ahmad Dahlan Journal of English Studies, 2022)
Only little research has explored how information from alternative assessments especially portfolios might be best utilized in developing second language acquisition processes of a single individual student’s comprehension of simple present tense as one of grammar aspects. To understand these ideas more complete, a greater initial has to be set on a study. In addition, there must be a more prominent center on how teachers can implement alternative assessment especially portfolio assessment and how the information from these assessments can be utilized to inform and direct the learning process. Using mix method design, this study examined the language processing of two students (i.e., a high-ability learner and a low-ability learner) studying at grade seventh at MTsN 4 surabaya. According to the findings, There was difference in the degree to which the high ability student accurately noticed the answers of the questions (the use of s/es in simple present tense), rather than the low ability student. Both low ability and high ability learners could recognize the learning gaps before and after the learning process, and they notice their development system towards the target language. However, the high ability student performed better.